The challenge of turning peers into active defenders - Seixas, Sónia Raquel Pereira Malta Marruaz (2020)
School bullying is responsible for a serious number of biopsychosocial eﬀects for students directly involved (1) and represents one of the highly important variables that inﬂuence mental health at school age. In addition, bullying is also a complex behaviour that occurs within a social context that goes beyond the interaction between the bully and the victim. As many other participants are involved, it becomes more clear that we should study bullying as a social phenomenon (2), by analysing the potential roles that peers play when facing bullying behaviour.